Mating type locus of Chinese black truffles reveals heterothallism and the presence of cryptic species within the T. indicum species complex. - Beatrice Belfiori (PLoS ONE, 2013)
Tuber spp. are filamentous ascomycetes which establish symbiosis with the roots of trees and shrub species. By virtue of this symbiosis they produce hypogeous ascocarps, known as truffles. Filamentous ascomycetes can reproduce by homothallism or heterothallism depending on the structure and organization of their mating type locus. The first mating type locus in a truffle species has been recently characterized in Tuber melanosporum and it has been shown that this fungus, endemic in Europe, is heterothallic. The availability of sequence information for T. melanosporum mating type genes is seminal to cloning their orthologs from other Tuber species and assessing their reproductive mode. Here we report on the organization of the mating type region in T. indicum, the black truffle species present in Asia, which is the closest relative to T. melanosporum and is characterized by an high level of morphological and genetic variability. The present study shows that T. indicum is also heterothallic. Examination of Asiatic black truffles belonging to different genetic classes, sorted according to the sequence polymorphism of the internal transcribed spacer rDNA region, has revealed sequence variations and rearrangements in both coding and non-coding regions of the mating type locus, to suggest the existence of cryptic species within the T. indicum complex. The presence of transposable elements within or linked to the mating type region suggests a role of these elements in generating the genotypic diversity present among T. indicum strains. Overall, comparative analyses of the mating type locus have thus allowed us to tackle taxonomical and phylogenetic issues within black truffles and make inferences about the evolution of T. melanosporum-T. indicum lineage. Our results are not only of fundamental but also of applied relevance as T. indicum produces edible fruit bodies that are imported also into Europe and thus may represent a biological threat for T. melanosporum.